Axonal transport of TDP-43 mRNA granules is impaired by ALS-causing mutations. - Alami, N.H.; Smith, R.B.; Carrasco, M.A.; Williams, L.A.; Winborn, C.S.; Han, S.S.; Kiskinis, E.; Winborn, B.; Freibaum, B.D.; Kanagaraj, A.; Clare, A.J.; Badders, N.M.; et al. (Neuron, 2014)
The RNA-binding protein TDP-43 regulates RNA metabolism at multiple levels, including transcription, RNA splicing, and mRNA stability. TDP-43 is a major component of the cytoplasmic inclusions characteristic of amyotrophic lateral sclerosis and some types of frontotemporal lobar degeneration. The importance of TDP-43 in disease is underscored by the fact that dominant missense mutations are sufficient to cause disease, although the role of TDP-43 in pathogenesis is unknown. Here we show that TDP-43 forms cytoplasmic mRNP granules that undergo bidirectional, microtubule-dependent transport in neurons in vitro and in vivo and facilitate delivery of target mRNA to distal neuronal compartments. TDP-43 mutations impair this mRNA transport function in vivo and in vitro, including in stem cell-derived motor neurons from ALS patients bearing any one of three different TDP-43 ALS-causing mutations. Thus, TDP-43 mutations that cause ALS lead to partial loss of a novel cytoplasmic function of TDP-43.